STRATEGI LITERASI INFORMASI DALAM MENINGKATKAN MINAT BACA SISWA SDN 10 RANTAU ALAI DESA SUKANANTI BARU - Febiola, Lolita Nurli; Vlora, Rani Kurnia (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM Azramedia indonesia, 2023)
The purpose of this study is to find out information literacy strategies in increasing students' reading interest at SDN 10 RANTAU ALAI SUKANANTI BARU VILLAGE.This research method uses qualitative descriptive approach research because it obtains words, images or behavior and is not expressed in statistical form. And the data used in this study is in the form of an explanation of data from informants orally, documentation and observing the location. In this study, the author focuses on information literacy strategies in increasing students' reading interest at SDN 10 RANTAU ALAI SUKANANTI BARU VILLAGE. The strategy carried out is the habituation stage, development by reading 10 to 15 minutes before class starts or after class starts and must visit the library. As well as the supporting factor stage, namely teacher support and student motivation and enthusiasm in wanting to read as well as enthusiastic support from parents and adequate book collections and inhibiting factors in increasing interest in reading, there are still students who lack enthusiasm in reading and lacking facilities such as tables and chairs in the library.